THE EFFECTS OF ANKLE STRATEGIES EXERCISE AND TANDEM WALKING EXERCISE IN ELDERLY PEOPLE WITH DYNAMIC BALANCE DISORDER - Shabira, Tania Ayu; Bustam, Ika Guslanda (Universitas Muhammadiyah Yogyakarta, 2022)
Introduction: The normal aging process affects all physiological processes in the elderly or that's called geriatric giants causing several problems, one of the loss of the ability is to maintain balance when walking. Purpose : This study aims to determine The effects of ankle strategies exercise and tandem walking exercise in elderly people with dynamic balance disorder. Methodology :Sixty elderly people participated in this study. They were separated into two groups with 30 participants in each group. First group were given ankle strategy and the second group were given tandem walking exercise. The balance test was used Time Up and Go Test (TUGT) and One Leg Standing (OLS) Test. The best TUG score and OLS (in seconds) of 3 trials in each condition was obtained for analysis. Results : Aftersix times a weeks during 4 weeks, there was increase dynamic balance ability value in elderly people. The result test using Paired Samples t-test in 1stgroup showed p = 0.000 (p > 0.05) and in the 2nd group showed p = 0.000 (p > 0.05) meaning that both treatments given to 1st and 2nd group had an effect on the balance improvement in elderly people. Therefore, no significant difference between the two groups. Originality :There were significant increase in the dynamic balance ability of elderly people after routinely getting ankle strategy exercise and tandem walking exercise aftersix times in a weeks during 4 weeks.